2006
DOI: 10.3727/000000006783981260
|View full text |Cite
|
Sign up to set email alerts
|

ZD6474, an Inhibitor of Vascular Endothelial Growth Factor Receptor Tyrosine Kinase, Inhibits Growth of Experimental Lung Metastasis and Production of Malignant Pleural Effusions in a Non-Small Cell Lung Cancer Model

Abstract: ZD6474 is a novel, orally active inhibitor of vascular endothelial growth factor receptor-2 (VEGFR-2) tyrosine kinase, with some additional activity against epidermal growth factor receptor (EGFR) tyrosine kinase. The purpose of this study was to determine the potential of ZD6474 in the control of established experimental lung metastasis and pleural effusions produced by human non-small cell lung cancer (NSCLC) cells. PC14PE6 (adenocarcinoma) and H226 (squamous cell carcinoma) cells express high levels of EGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 0 publications
2
31
0
1
Order By: Relevance
“…The concentrations of E7080 required to inhibit endothelial proliferation was lower, as was the dose needed to show antimetastatic effects (10 vs. 50 mg/kg; refs. 25,37,38). Furthermore, we found that E7080 prolonged survival in mice bearing multiple organ metastases of SBC-5 cells those with pleural effusion caused by PC14PE6 cells, clearly indicating that E7080 is a highly active inhibitor of angiogenesis of lung cancers with nonmutant EGFR.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The concentrations of E7080 required to inhibit endothelial proliferation was lower, as was the dose needed to show antimetastatic effects (10 vs. 50 mg/kg; refs. 25,37,38). Furthermore, we found that E7080 prolonged survival in mice bearing multiple organ metastases of SBC-5 cells those with pleural effusion caused by PC14PE6 cells, clearly indicating that E7080 is a highly active inhibitor of angiogenesis of lung cancers with nonmutant EGFR.…”
Section: Discussionmentioning
confidence: 65%
“…However, lung lesions produced by SBC-5 cells were smaller than 2 mm in diameter and had few endothelial cells and lymph endothelial cells. In sharp contrast, PC14PE6 cells, which produce high amounts of VEGF, give rise to highly angiogenic and lymphangiogenic lung lesions greater than 2 mm in diameter (9,25). E7080 decreased the number of endothelial cells, lymph endothelial cells, and proliferating cells in PC14PE6 lung lesions, but it did not in SBC-5 lung lesions with few endothelial cells and lymph endothelial cells (Supplementary Figs.…”
Section: Discussionmentioning
confidence: 99%
“…For the EGFR sequence, DNA was extracted from each cell line using a QIAamp DNA Mini kit (Qiagen) and the exons encoding the intracellular domain (exons [18][19][20][21][22] were amplified by PCR. Primer sequences and amplification conditions have been described previously (3).…”
Section: Methodsmentioning
confidence: 99%
“…A combination of bevacizumab with erlotinib seemed to have clinical benefit in the treatment of nonsquamous NSCLC (19). Vandetanib (ZACTIMA) is an orally available multitarget TKI inhibiting VEGFR-2, with additional inhibition of EGFR and rearranged during transfection (RET) receptor signaling (20)(21)(22). Vandetanib has shown promising results in phase II clinical trials in patients with pretreated NSCLC (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Antibody treatment, to a lesser degree, also inhibited tumor growth [59,60,95,96] and prolonged the survival of mice inoculated with tumor cells [59]. Comparable preclinical efficacy was seen with tyrosine kinase inhibitors targeting VEGF receptors [97,98] or with a soluble VEGF decoy receptor inhibiting VEGF [67,99], and after i.p. infusion of a VEGF antisense oligonucleotide [100], but not with conventional chemotherapy applied i.p.…”
Section: Inhibition Of Vegf Activity As a Targeted Therapy For Malignmentioning
confidence: 99%